Nukleosinteza velikega poka - Gajer, Alen (Matrika, 2022)
Big Bang nucleosynthesis is a theory that explains how the first nuclei after the Big Bang were made and what were their primordial abundances. In the first half of the article we will explain the theory and its predictions. In the second half we will present the measurements and compare the results with the predictions of the theory. At the end we will also touch on the still unsolved problem of the theory and some possible solutions.
Keywords: Big Bang; cosmology; first nuclei; kozmologija; nucleosynthesis; nukleosinteza; prvotna jedra; veliki pok